Evaluation of Treated and Untreated Sludge from Yarn Processing Factory as Adsorbent Candidates for Dye Removal - Muhammad Abbas Ahmad Zaini (Science Faculty of Chiang Mai University, 2019)
This work was aimed to evaluate the adsorptive characteristics of yarn sludge for methylene blue removal. The sludge was chemically treated using H3PO4, HCl and KOH, while the untreated sludge was also employed for reference. The adsorbents were characterized by specific surface area and surface functional groups. Methylene blue adsorption was carried out at room temperature, and the adsorption data were analyzed using isotherm and kinetics models. The equilibrium data could be well described using Langmuir model, indicating that the adsorption is monolayer in nature. The kinetics data are fitted to both pseudo-first order and pseudo-second order models. Results show that the maximum removal of methylene blue was observed to have the following order: untreated > KOH-treated > HCl-treated > H3PO4-treated. The maximum adsorption capacity for untreated yarn sludge was found to be 279mg/g. Results also indicate that the sludge could be used as effective adsorbent for methylene blue dye removal.